Colonization of methicillin-resistant Staphylococcus aureus among healthcare students: an integrative review - Oliveira, Erika Morganna Neves de (2021)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) infection is a worldwide concern given its presence even in non-hospitalized healthy individuals, such as university students OBJECTIVE: To identify in the literature the prevalence of colonization by MRSA among healthcare students. DESIGN AND SETTING: Integrative review of the literature conducted in Universidade Federal do Piauí. METHOD: A search for primary studies was performed in the following databases: Medical Literature Analysis and Retrieval System on-line; Cumulative Index to Nursing and Allied Health Literature; Web of Science; Scopus; and LILACS. RESULTS: This review included 27 studies that demonstrated MRSA infection prevalence ranging from 0.0 to 15.3% among students. CONCLUSION: The prevalence of colonization of MRSA among healthcare students is high, and the nasal cavity was cited as an important reservoir location for these microorganisms.